PENGARUH MEDIA VIRTUAL BERBASIS KEARIFAN LOKAL BERBANTUAN SMART APPLICATION CREATOR PADA MATERI OPTIK TERHADAP KEMAMPUAN BERPIKIR KRITIS SISWA SMA - Irawati Irawati; Nana Mardiana; Sheila Fitriana; Tuti Hardianti; Syahwin Syahwin; Rachmat Rizaldi (JURNAL PEMBELAJARAN FISIKA, 2023)
This study aims to determine the impact of local wisdom-based virtual media assisted by smart application creators on optical material on high school students' critical thinking skills. Purposive sampling was used as a research sampling strategy in a quasi experiment and used a nonequivalent control group design. The experimental class set was class XI-MIPA 1, while the control class selected was class XI-MIPA 2. In July 2022, this research was carried out at SMAS PAB 8 Saentis. Students' capacity to think critically was assessed as part of the data collection process. The results of the study show that local wisdom-based virtual media assisted by smart application creators on optical material has an impact on high school students' critical thinking skills. The t test at = 0.05 obtained sig. (2-tailed) is 0.00, the average value of N-Gain in the control class is 0.53, and the experimental class is 0.74. Observations show that this method increases the progress of critical thinking skills in the aspect of drawing conclusions 84.3 %, identifying assumptions 80.4%, reasoning deductively 75.2%, making logical interpretations 65%, and evaluating arguments 88.2%